Development of a pressure recovery unit for seawater reverse osmosis system - Tan, Yu En (2008)
As supplies of clean water diminish, more countries are turning to desalination to meet their fresh water needs. However, it is an energy intensive process due to the high pressure needed to overcome the osmotic pressure of ocean water. Energy recovery devices (ERDs) are commonly used to lower the energy consumption of the reverse osmosis (RO) process. Using the most efficient ERDs currently available, the lowest energy consumption that has been achieved is 1.9 kWh/m3 of clean water processed. The main objective of this thesis is to develop a novel ERD capable of further reduction in the energy consumption of the RO process. A working prototype was fabricated and tested successfully up to 20 bar of pressure.